Method for testing swelling ratio of colloid and application

By preparing solid colloid samples in a fixed mold and measuring their thickness changes, the colloid swelling rate is calculated, which solves the problem of difficult to test and screen suitable gel-coated separator colloid materials in the prior art, and improves the battery capacity and performance.

CN119595532APending Publication Date: 2025-03-11EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411930391.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

It is difficult for the prior art to effectively test and screen out colloidal materials suitable for preparing glue-coated separators, especially the swelling rate of colloidal materials has an important impact on the coating structure and battery performance.

Method used

The solid colloid sample was prepared in a fixed mold, and the colloid swelling rate was calculated by measuring the thickness of the solid colloid sample before and after soaking the electrolyte. This method reduces the application scenario of colloids in batteries, and the swelling rate calculated by thickness changes meets the performance indicators of colloids themselves.

Benefits of technology

Through this test method, the colloid swelling rate can be accurately measured, thereby screening out colloidal materials suitable for preparing glue-coated separators to improve the capacity and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595532A_ABST
    Figure CN119595532A_ABST
Patent Text Reader

Abstract

The invention provides a colloid swelling ratio testing method and application. The testing method comprises the following steps: (1) preparing a solid colloid sample in a mold; (2) measuring the initial thickness of the solid colloid sample, and recording the initial thickness as D0; (3) adding an electrolyte into the mold, enabling the solid colloid sample to be completely immersed in the electrolyte, performing soaking, measuring the thickness of the soaked solid colloid sample, and recording the thickness as Dx; and calculating the swelling ratio of the colloid according to a formula that the swelling ratio is equal to (D0-Dx) / D0 * 100%. The colloid swelling ratio can be measured by adopting the testing method, so that a colloid material suitable for preparing a glued diaphragm can be screened out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a test method for colloid swelling rate and application thereof. Background Art

[0002] The coated diaphragm is a key material that plays an important role in the field of electrochemical energy storage such as lithium-ion batteries. It includes a diaphragm body and one or more layers of colloidal coating coated on the surface of the diaphragm body. Common diaphragm body materials include polyolefin diaphragms, such as polyethylene (PE) and polypropylene (PP). These polyolefin diaphragms have a porous structure. Their function is to physically separate the positive and negative electrodes inside the battery to prevent the positive and negative electrodes from directly contacting and short-circuiting, while allowing lithium ions to freely transfer through their pores during the charge and discharge process. The main function of the colloidal coating is to enhance the function of the diaphragm, such as improving the adhesion between the diaphragm and the electrode, improving the thermal stability of the diaphragm, and enhancing the wettability of the diaphragm to the electrolyte.

[0003] In the colloidal coating of the coated diaphragm, the swelling rate of the colloidal material has an important influence on the coating structure. If the swelling rate of the colloidal material is too large, it will damage the structure of the colloidal coating and affect the transmission of lithium ions by the diaphragm, thereby causing the battery capacity to decrease. Therefore, it is necessary to select a colloidal material with a lower swelling rate in the electrolyte to prepare the coated diaphragm.

[0004] Therefore, there is an urgent need to provide a method for testing the swelling rate of colloidal materials in order to screen out colloidal materials suitable for preparing coated diaphragms. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a test method and application of colloid swelling rate. The present invention prepares a solid colloid sample in a fixed mold, and then measures the thickness of the solid colloid sample before and after immersion in an electrolyte to calculate the colloid swelling rate. Therefore, the colloid swelling rate can be measured by the test method of the present invention, so that the colloid material suitable for preparing the coated diaphragm can be screened out.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for testing the swelling rate of a colloid, the method comprising:

[0008] (1) Prepare a solid colloidal sample in a mold.

[0009] (2) Measure the initial thickness of the solid colloidal sample and record it as D0.

[0010] (3) Add electrolyte to the mold so that the solid colloidal sample is completely immersed in the electrolyte for soaking. Measure the thickness of the solid colloidal sample after soaking, which is recorded as D x; By formula: Swelling rate = (D0-D x ) / D0×100%, and calculate the colloid swelling rate.

[0011] The present invention provides a method for testing the swelling rate of a colloid, wherein a solid colloid sample is prepared in a fixed mold, and then the swelling rate of the colloid is calculated by measuring the thickness of the solid colloid sample before and after immersion in an electrolyte. The testing method of the present invention restores the application scenario of the colloid in the battery, and the swelling rate calculated by the thickness change conforms to the performance index of the colloid itself. The swelling rate of the colloid can be measured by the testing method of the present invention, so that the colloid material suitable for preparing the coated diaphragm can be screened out.

[0012] The present invention does not limit the shape of the bottom surface of the mold. For example, it can be square or round, etc., wherein the side length of the square mold can be 1-1000mm, for example, it can be 1mm, 5mm, 10mm, 100mm, 500mm or 1000mm, etc.

[0013] Preferably, the thickness of the solid colloid sample before and after immersion in the electrolyte is measured by a grating ruler displacement sensor.

[0014] Preferably, the specific steps of preparing the solid colloidal sample in the mold include:

[0015] The glue liquid containing the glue material to be tested is placed in a mold and baked until the surface is dry to obtain a solid colloid sample.

[0016] Preferably, the solvent in the glue solution includes N-methylpyrrolidone (NMP) or DI water.

[0017] Preferably, the baking temperature is 60-90°C, for example, it can be 60°C, 62°C, 65°C, 67°C, 70°C, 72°C, 75°C, 77°C, 80°C, 82°C, 85°C, 87°C or 90°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In the present invention, if the baking temperature is too low, the solid colloidal sample cannot be dried and cannot be obtained; if the baking temperature is too high, the solid colloidal sample may melt.

[0019] Preferably, the baking time is 12-24 hours, for example, it can be 12 hours, 13 hours, 15 hours, 17 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the baking is performed under blowing conditions.

[0021] The baking step of the present invention can be carried out by blowing air under vacuum conditions or non-vacuum conditions.

[0022] Preferably, the baking is performed under vacuum conditions.

[0023] The invention performs blast baking under vacuum conditions, which is beneficial to accelerating the baking speed and shortening the baking time.

[0024] Preferably, the baking is carried out in a vacuum blower dryer.

[0025] Preferably, the vacuum degree of the vacuum condition is 10 -5 -10 -1 Pa, for example, can be 10 -5 Pa, 10 -4 Pa, 10 -3 Pa, 10 -2 Pa or 10 -1 Pa, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the total duration of the soaking in step (3) is recorded as T, and T satisfies: 0<T≤312h. T can be, for example, 0.1h, 0.2h, 0.5h, 1h, 2h, 5h, 10h, 12h, 24h, 30h, 50h, 72h, 120h, 168h or 312h, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0027] Preferably, during the soaking process of step (3), the thickness of the solid colloid sample after soaking is measured once at every time interval t, and the colloid swelling rate is calculated, so as to obtain the colloid swelling rate corresponding to different soaking times; wherein, t satisfies: 0.5h≤t≤144h, and t can be, for example, 0.5h, 1h, 2h, 3h, 5h, 6h, 10h, 12h, 24h, 30h, 48h, 50h, 72h, 120h or 144h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] It should be noted that the interval time t corresponding to each thickness measurement may be the same or different.

[0029] Preferably, a swelling curve of the colloid in the electrolyte is plotted with the immersion time as the abscissa and the colloid swelling rate as the ordinate, and the maximum value of the ordinate of the swelling curve is the limiting swelling rate.

[0030] In the present invention, according to the colloid swelling rate data corresponding to different immersion times, the swelling curve of the colloid in the electrolyte is plotted with the immersion time as the horizontal axis and the colloid swelling rate as the vertical axis, thereby obtaining the limiting swelling rate. According to the limiting swelling rate, the colloid material suitable for preparing the coated diaphragm can be further screened.

[0031] In a second aspect, the present invention provides a test method as described in the first aspect for use in testing the swelling rate of colloid in a glue-coated diaphragm.

[0032] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention provides a method for testing the swelling rate of a colloid, wherein a solid colloid sample is prepared in a fixed mold, and then the swelling rate of the colloid is calculated by measuring the thickness of the solid colloid sample before and after immersion in an electrolyte. The testing method of the present invention restores the application scenario of the colloid in the battery, and the swelling rate calculated by the thickness change conforms to the performance index of the colloid itself. The swelling rate of the colloid can be measured by the testing method of the present invention, so that the colloid material suitable for preparing the coated diaphragm can be screened out. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The swelling curves provided for Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention is further described below by specific implementation methods. For ease of understanding the present invention, the present invention lists the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0037] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0038] Three kinds of adhesives containing acrylonitrile-styrene (AS) copolymers were provided. The AS in the three adhesives was recorded as AS-01, AS-02 and AS-03 according to the different molecular weights. The solvent in each adhesive was NMP. AS-01, AS-02 and AS-03 were purchased from Jinli New Energy Technology Co., Ltd., Enjie New Materials Co., Ltd. and Sinoma Lithium Membrane Co., Ltd.

[0039] Example 1

[0040] This embodiment provides a method for testing the swelling rate of a colloid, and the testing method comprises the following steps:

[0041] (1) Add the glue containing AS-01 into a square mold with a side length of 500 mm. -3 Pa and a temperature of 80°C, vacuum blast baking was performed for 20 h. After taking out, the surface was wiped with dust-free paper without any residue, indicating that the surface was dry and a solid colloidal sample was obtained.

[0042] (2) Measure the initial thickness of the solid colloidal sample and record it as D0.

[0043] (3) Add lithium hexafluorophosphate electrolyte to the mold so that the solid colloidal sample is completely immersed in the electrolyte for soaking. After soaking for 0.5 h, 1 h, 2 h, 3 h, 6 h, 12 h, 24 h, 72 h, 120 h, 168 h and 312 h, the thickness of the solid colloidal sample after soaking is measured and recorded as D1, D2, D3, D4, D5, D6, D7, D8, D9, D10, D11, D12, D13, D14, D15, D16, D17, D18, D19, D20, D21, D22, D23, D24, D25, D26, D27, D28, D29, D30, D31, D32 10 and D 11 ; By formula: Swelling rate = (D0-D x ) / D0×100% to calculate the colloid swelling rate corresponding to different immersion times, where x is 1-11.

[0044] Based on the above method, samples 1, 2 and 3 were prepared, and 3 parallel experiments were conducted. The three sets of thickness data measured are shown in Table 1. The colloid swelling rate was calculated according to the data in Table 1, and the colloid swelling rates calculated for the same immersion time of samples 1, 2 and 3 were averaged. The final swelling rate data are shown in Table 2.

[0045] Example 2

[0046] This embodiment provides a method for testing the swelling rate of a colloid, and the testing method comprises the following steps:

[0047] (1) Add the glue containing AS-02 into a square mold with a side length of 500 mm. -3 Pa and a temperature of 80°C, vacuum blast baking was performed for 20 h. After taking out, the surface was wiped with dust-free paper without any residue, indicating that the surface was dry and a solid colloidal sample was obtained.

[0048] (2) Measure the initial thickness of the solid colloidal sample and record it as D0.

[0049] (3) Add lithium hexafluorophosphate electrolyte to the mold so that the solid colloidal sample is completely immersed in the electrolyte for soaking. After soaking for 0.5 h, 1 h, 2 h, 3 h, 6 h, 12 h, 24 h, 72 h, 120 h, 168 h and 312 h, the thickness of the solid colloidal sample after soaking is measured and recorded as D1, D2, D3, D4, D5, D6, D7, D8, D9, D10, D11, D12, D13, D14, D15, D16, D17, D18, D19, D20, D21, D22, D23, D24, D25, D26, D27, D28, D29, D30, D31, D32 10 and D 11 ; By formula: Swelling rate = (D0-D x ) / D0×100% to calculate the colloid swelling rate corresponding to different immersion times, where x is 1-11.

[0050] Based on the above method, samples 1, 2 and 3 were prepared, and 3 parallel experiments were conducted. The three sets of thickness data measured are shown in Table 1. The colloid swelling rate was calculated according to the data in Table 1, and the colloid swelling rates calculated for the same immersion time of samples 1, 2 and 3 were averaged. The final swelling rate data are shown in Table 2.

[0051] Example 3

[0052] This embodiment provides a method for testing the swelling rate of a colloid, and the testing method comprises the following steps:

[0053] (1) Add the glue containing AS-03 into a square mold with a side length of 500 mm. -3 Pa and a temperature of 80°C, vacuum blast baking was performed for 20 h. After taking out, the surface was wiped with dust-free paper without any residue, indicating that the surface was dry and a solid colloidal sample was obtained.

[0054] (2) Measure the initial thickness of the solid colloidal sample and record it as D0.

[0055] (3) Add lithium hexafluorophosphate electrolyte to the mold so that the solid colloidal sample is completely immersed in the electrolyte for soaking. After soaking for 0.5 h, 1 h, 2 h, 3 h, 6 h, 12 h, 24 h, 72 h, 120 h, 168 h and 312 h, the thickness of the solid colloidal sample after soaking is measured and recorded as D1, D2, D3, D4, D5, D6, D7, D8, D9, D10, D11, D12, D13, D14, D15, D16, D17, D18, D19, D20, D21, D22, D23, D24, D25, D26, D27, D28, D29, D30, D31, D32 10 and D 11 ; By formula: Swelling rate = (D0-D x ) / D0×100% to calculate the colloid swelling rate corresponding to different immersion times, where x is 1-11.

[0056] Based on the above method, samples 1, 2 and 3 were prepared, and 3 parallel experiments were conducted. The three sets of thickness data measured are shown in Table 1. The colloid swelling rate was calculated according to the data in Table 1, and the colloid swelling rates calculated for the same immersion time of samples 1, 2 and 3 were averaged. The final swelling rate data are shown in Table 2.

[0057] Table 1

[0058]

[0059] Table 2

[0060]

[0061]

[0062] It can be seen from the data in Table 2 that the swelling rate of the solid colloidal samples of Examples 1-3 is negative at the beginning of immersion. This is because the immersion time is short at the beginning, the molecular structure of the solid colloidal sample is not destroyed, and the electrolyte enters the gap of the colloidal sample structure, causing the sample to swell slightly. After immersion for a period of time, the swelling rate becomes positive. This is because the electrolyte and the colloidal sample undergo molecular diffusion, the molecular chain of the colloidal sample is broken and presents a viscous flow state, softening, and the thickness becomes smaller.

[0063] According to the data in Table 2, the swelling curve of the colloid in the electrolyte is plotted with the immersion time as the horizontal axis and the colloid swelling rate as the vertical axis. The swelling curves of Examples 1-3 are as follows: Figure 1 As shown in the figure, the limiting swelling rate of the colloidal material in Example 1 is 69.4%, the limiting swelling rate of the colloidal material in Example 2 is 82.3%, and the limiting swelling rate of the colloidal material in Example 3 is 76.4%. The colloidal materials in Examples 1 and 2 both reach maximum swelling after being immersed in the electrolyte for 120 hours, while the colloidal materials in Example 3 reach maximum swelling after being immersed in the electrolyte for 168 hours. The swelling degree of Example 1 is the smallest, and the swelling degree of Example 2 is the largest; therefore, Example 1 is more suitable for preparing the colloidal coating of the coated diaphragm.

[0064] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for testing the swelling rate of a colloid, characterized in that: The test method includes: (1) Preparing a solid colloidal sample in a mold; (2) measuring the initial thickness of the solid colloidal sample, recorded as D0; (3) Add electrolyte to the mold so that the solid colloidal sample is completely immersed in the electrolyte for soaking. Measure the thickness of the solid colloidal sample after soaking, which is recorded as D x ; By formula: Swelling rate = (D0-D x ) / D0×100%, and calculate the colloid swelling rate.

2. The testing method according to claim 1, characterized in that: The specific steps of preparing the solid colloid sample in the mold include: The glue liquid containing the glue material to be tested is placed in a mold and baked until the surface is dry to obtain a solid colloid sample.

3. The testing method according to claim 2, characterized in that: The baking temperature is 60-90°C.

4. The testing method according to claim 2 or 3, characterized in that: The baking time is 12-24 hours.

5. The testing method according to any one of claims 2 to 4, characterized in that: The baking is carried out under forced air conditions.

6. The testing method according to any one of claims 2 to 5, characterized in that: The baking is performed under vacuum conditions.

7. The testing method according to claim 6, characterized in that: The vacuum degree of the vacuum condition is 10 -5 -10 -1 Pa.

8. The testing method according to any one of claims 1 to 7, characterized in that: The total duration of the soaking in step (3) is denoted as T, and T satisfies: 0<T≤312h.

9. The testing method according to claim 8, characterized in that: During the soaking process of step (3), the thickness of the solid colloid sample after soaking is measured once every time interval t, and the colloid swelling rate is calculated, so as to obtain the colloid swelling rate corresponding to different soaking times; wherein t satisfies: 0.5h≤t≤144h; Preferably, a swelling curve of the colloid in the electrolyte is plotted with the immersion time as the abscissa and the colloid swelling rate as the ordinate, and the maximum value of the ordinate of the swelling curve is the limiting swelling rate.

10. A test method as claimed in any one of claims 1 to 9, applied to test the swelling rate of colloid in a rubber-coated diaphragm.